Persepsi dan Kesiapan Mengajar Mahasiswa Guru Terhadap Anak Berkebutuhan Khusus dalam Konteks Sekolah Inklusi - M. Kusuma Wardhani (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2020)
The implementation of inclusive education in reality, really requires readiness and support from various parties, including fron the educators who are ready in the sense of being able and willing to educate children with special needs. The focus of this study is to examine the perceptions of pre-service teachers in Pelita Harapan University for children with special needs who have access to inclusive education, and what factors underlie these perceptions. The next focus is whether the pre-service teachers have the readiness or vice versa just that there is still doubt or reluctance to teach in inclusive schools. The research method is qualitative descriptive. The number of respondents was one class consisting of 40 students which was a combination of 2 two study programs. The results showed that pre service teachers had perceptions that children with special needs could attend school in inclusive schools, and will be successfull. The arguments that underlie these perceptions are three things: the equal right to education for everyone; curriculumadjustment, teaching methods, assessments and facilities for students with special needs; inclusive schools are a combination of public schools with special schools, and adjustments for each child with special needs in the form of PPI (Individual Development Program). All respondents stated their readiness to teach in inclusive schools. The reason are because a teacher should treat his student equally, the subject of Teaching Student With Special Ability courses has equipped them, and adjustments made in inclusive schools in terms of methods, curriculum, assessment and infrastructure.